Learning about spatial inequalities: Capturing the heterogeneity in the urban environment. (10th November 2019) - Siqueira-Gay, Juliana; Giannotti, Mariana; Sester, Monika
Abstract: Transportation systems can be conceptualized as an instrument of connecting people and their activities over the territory, playing an important role in developing sustainable cities. The current rationale of transport provision is based on population demand and rarely considers the potential of minimizing spatial disparities and uneven distribution of services. To meet the challenge of supporting a more equitable resources distribution, this work aims at identifying and describing patterns of urban services supply, their accessibility, and household income. By using a multidimensional approach, the spatial inequalities of a large city of the global south reveal that the low-income population has low access mainly to hospitals and cultural centers. A low-income group presents an intermediate level of accessibility to public schools and sports centers, evidencing the diverse condition of citizens in the peripheries. These complex outcomes generated by the interaction of land use and public transportation emphasize the importance of comprehensive methodological approaches to support decisions of urban projects, plans and programs. Reducing spatial inequalities, especially providing services for deprived groups, is fundamental to promote the sustainable use of resources and optimize the daily commuting. Graphical abstract: Image 1 Highlights: A multidimensional approach evidences different level of inequalities distribution. Spatial inequalities of a global south megacity São Paulo (Brazil) are explored. Diverse socioeconomic groups with different accessibility levels are mapped. Low income groups have low accessibility mainly to hospitals and culture centers. In the periphery, a heterogeneous condition of accessibility is identified.